Using Blended Learning to Increase Students’ English Learning Motivation - Nurdiana, Nurdiana; Afrizal, Afrizal; Roswati, Roswati; Damayanti, Indah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
The goal of this study was to look at students' motivation for English studying at Cendana Senior High School in Pekanbaru. The researchers utilized a descriptive quantitative technique. There were 113 pupils in third grade, divided into four classrooms. The researchers employed a purposive selection strategy to choose 30 pupils from this group. The researchers employed questionnaires to collect data. According to the study's results, the degree of blended-learning students' English learning motivation was 73,2%, indicating that the students were well motivated. In this study, the instrumental factor was found to be the most crucial component in students' motivation for English blended learning. Blended learning is fascinating to the instructor and students because it allows them to exercise English in several ways. Students can learn not only by seeing and hearing the instructor in front of the class on a chalkboard but also by the teacher's excitement and personal characteristics. Students may get more engaged in studying English through various techniques, and they may also exercise their knowledge through blended learning. There might be other explanations from films or music.